Specificity of the bacteriophage Mu mom+ -controlled DNA modification. - Hattman, S (1980)
Bacteriophage Mu DNA was labeled after induction in the presence of [8-3H]adenine. Purified DNA was enzymatically digested, and the 3H-labeled dinucleotides were isolated. Approximately 15 to 20% of the adenine residues were modified to a new form, Ax, as observed previously (S. Hattman, J. Virol. 32:468-475, 1979) in bulk DNA. Paper electrophoretic analysis revealed that only two dinucleotide species contain Ax, namely, (Ax,C) and (Ax,G). The observation that only C and G are the nearest neighbors of Ax is consistent with the proposal of Kahmann and Kamp (R. Kahmann and D. Kamp, J. Mol. Biol., in press) that modification of Mu DNA occurs at the A residue within the pentanucleotide sequence, 5'...(CG)-A-(GC)-N-Py...3'.